Aproximações à história do gênero épico na TV brasileira : um estudo sobre a minissérie A muralha (TV Globo, 2000) - Santos Junior, Cid José Machado dos (2014)
This research presents the investigation of the epic genre´s manifestations within Brazilian audiovisual environment having as object the miniseries A muralha (TV Globo, 2000), based on the novel A muralha (1954) by Dinah Silveira de Queiroz, written by Maria Adelaide Amaral and directed by Denise Saraceni, Carlos Araújo and Luís Henrique Rios. The intersections between the productive practices of TV Globo and the referential legacy of the epic genre in film and television fields are discussed, taking into account aspects of interculturalism and the context of the celebrations of the 500th anniversary of the discovery of Brazil, a period marked by a boom of historic telefictions and the modernization of production strategies and marketing of audiovisual works made by the television network. The work performs an approximation to the binomial TV-cinema relationship in the open television programming and how this articulated the epic genre in his schedule in primetime serial form.